Methane hydrates – Australian perspective - Koltun, P.; Klymenko, V. (Розробка родовищ, 2016)
Purpose. To analyze Australian methane hydrate resources, exploration, and production, its current state and future potential. Methods. Analysis of data published in different sources concerned with geological surveys and government reports related to Australian natural gas reserves, production and consumption of gas in Australia. Analysis of theoretical and experimental research into methane hydrates properties and prevention of gas hydrate deposits formation in pipes during production and transportation of natural gas. Findings. The study of gross figures associated with the present state of gas production in Australia testified that enough gas is extracted to meet the current needs. Increase in natural gas consumption in future creates good chances for developing gas production from unconventional deposits, specifically getting methane from gas hydrates deposits. While predicting main trends in the efficient exploration and use of methane hydrates resources it is necessary to consider their possible impact on the environment. Originality. On the basis of the conducted analysis, the current state of methane hydrates research in Australia is examined. For its gas industry, it is critical to estimate their reserves and assess methane extraction from gas hydrates deposits in the near future. Practical implications. The obtained results can be used to evaluate the investment attractiveness of future exploration of methane hydrates resources in Australia.